2020
DOI: 10.1016/s2352-4642(20)30177-2
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in children and adolescents in Europe: a multinational, multicentre cohort study

Abstract: Background To date, few data on paediatric COVID-19 have been published, and most reports originate from China. This study aimed to capture key data on children and adolescents with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection across Europe to inform physicians and health-care service planning during the ongoing pandemic. Methods This multicentre cohort study involved 82 participating health-care institutions across 25 European countries, using a well established research network-the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

133
1,291
24
95

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,146 publications
(1,543 citation statements)
references
References 29 publications
133
1,291
24
95
Order By: Relevance
“…Atypical presentations like seizures (10.6%) and gastrointestinal symptoms (12.2%) were more common as compared to other studies. [7,9,12,14] Seizure and diarrhea as presenting symptoms was more common in Group I.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Atypical presentations like seizures (10.6%) and gastrointestinal symptoms (12.2%) were more common as compared to other studies. [7,9,12,14] Seizure and diarrhea as presenting symptoms was more common in Group I.…”
Section: Discussionmentioning
confidence: 92%
“…(Table II) A systematic review in adults concluded that co-morbidities like Hypertension, Cardiovascular disease, Diabetes, and chronic renal diseases were signi cantly associated with mortality [20]. A study of children from the European cohort concluded that neonates, male sex, pre-existing medical conditions, fever, lower respiratory tract infection, radiological changes of pneumonia or ARDS, and viral co-infection were associated with more severe course on univariate analysis; however, the study did not compare these parameters to mortality [14]. In our cohort, male sex, hypoxia (SpO2 <94% ) on admission, need for respiratory support, inotropes, intensive care, length of hospital stay <10 days was signi cantly associated with mortality on univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…According to the currently available evidence, SARS-CoV-2 infection in children is rarely associated with severe disease ( 1 ), children are less likely to be infected compared with adults, and children are likely to be less infectious compared with infective adults ( 2 , 3 ). However, multiple cases of children with a new hyperinflammatory condition in children subsequent to SARS-CoV-2 infection have been reported in Europe and the United States of America ( Tables 1 , 2 ).…”
Section: Statementmentioning
confidence: 99%
“… a lower frequency of infection [ 1 ], [ 2 ], [ 3 ], [ 4 ], [ 5 ] (some, but by far not all studies were conducted during the lockdown, which is a methodological limitation); a lower average severity of disease and associated with this; a significantly lower risk of the most serious, including fatal, courses; from CoVID-19 [ 6 ], [ 7 ], [ 8 ], [ 9 ], [ 10 ], [ 11 ], [ 12 ], [ 13 ], [ 14 ], [ 15 ], [ 16 ], [ 17 ], [ 18 ], [ 19 ], [ 20 ], [ 21 ], [ 22 ], [ 23 ], [ 24 ]. …”
Section: Introductionmentioning
confidence: 99%